Three-year treatment outcomes with three brands of implants placed in the posterior maxilla and mandible of partially edentulous patients - ÖZKAN, YASEMİN; ÖZKAN, YAŞAR (MOSBY-ELSEVIER, 2007)
Statement of problem. Survival rates of implants in posterior regions vary among clinical studies. Problems occur more often in the posterior segment of the maxilla due to proximity of the maxillary sinus and reduced quality or quantity of alveolar bone. Purpose. This clinical study evaluated the treatment outcomes of 3 brands of implants in the posterior maxillac and mandibles of 63 patients. Treatment outcomes of all implants were assessed according to implant type, location, patient gender, periodontal status, and prosthesis type. Material and methods. A total of 203 implants - 105 ITT (ITT), 53 Camlog (CAM), and 45 Frialit (FRI) - were placed in 63 patients (38 women, 25 men). One hundred twelve implants were located in the posterior mandible and 91 in the posterior maxilla. All implants were longer than 10 mm and had a diameter larger than 3.5 mm. Implants in the ITT group were placed in a 1-stagc surgery. The CAM and FRI groups were treated with a 2-stage surgical protocol. Implants were not loaded until osseointegration was complete, which was determined clinically and radiographically. At that point, implants were restored with 50 single crowns and 81 fixed partial dentures (FPDs). While 11 FPDs connected implants to natural teeth, 70 FPDs were supported by implants only. Standardized radiographs were made, and clinical parameters were recorded at prosthesis insertion (baseline) and at each recall evaluation (6, 12, 24, and 36 months). Plaque index (PT), sulcus bleeding index (SBI), peri-implant probing depth (PD), and radiographic marginal bone loss (MBL) levels were recorded at baseline, along with any biological and mechanical complications. Repeated-measures ANOVA, Kruskal-Wallis test, Wilcoxon signed rank test, and paired samples tests were used for statistical analysis (alpha = .05). Results. One implant was lost during the osseointegration period in I woman due to infection. The cumulative implant treatment outcome was 99.3%. At the 3-year recall, plaque accumulation was significantly higher than baseline scores (P = .01, Wilcoxon signed rank test). Eight percent of the patients presented >2 mm PD at 2-year recall. The influence of observation time was found to be significant for the mean MBL values between groups (P = .001). When MBL values were compared between groups, no significant differences were found. For I patient in the FRI group, abutment loosening was observed and both the crown and the abutment were replaced. Patient satisfaction in all groups was high. Conclusion. The 3 brands of implants evaluated in this study exhibited similar positive treatment outcomes after 3 years.
Keywords: FIXED PARTIAL DENTURES; LONG-TERM EVALUATION; LIFE TABLE ANALYSIS; PROSPECTIVE MULTICENTER; ENDOSSEOUS IMPLANTS; CLINICAL-EVALUATION; RESTORATIONS; SURVIVAL; JAWS